Pengaruh Keputusan Investasi terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Intervening (Studi Kasus pada Perusahaan Pertambangan yang Tercatat di BEI Periode 2015-2018) - Bambang Mahmudi; Enis Khaerunnisa (Sains: Jurnal Manajemen dan Bisnis, 2020)
This research aims to test investment decisions affecting the value of the company by using the dividend policy as a intervening variable. In this study, the company's value was measured with the Price to Book Value (PBV), the investment decision measured by the Total Assets Growth (TAG), and the dividend policy was quantified by Divident Pay Out Ratio. Samples in this research are mining industry sector companies that distribute dividends listed on Indonesia Stock Exchange period 2015 – 2018. Sample determination method using purposive sampling. The methods of analysis used are classical assumption test, partial test (t test), path analysis, and Sobel test. Based on the results of the analysis data that (1) the investment decision (TAG) has a positive and insignificant effect on the company's value (PBV), (2) The investment decision (TAG) is negatively and insignificant in the dividend policy (DPR), (3) Dividend policy (DPR) affects negative and not significant to the company's value (PBV), (4) Dividend policy (DPR) is not able to distribute the influence of investment decision (TAG) on the company's value (PBV).